Windows Phone 7 programming LiveLessons : developing applications for the Windows Phone - Wolfe, Kevin (SAMS, 2011)
"In 24 hands-on video lessons, Microsoft MVP Kevin Wolf shows you how to get started developing applications for Microsoft's Windows Phone platform. Kevin starts with the basics for developing both Silverlight and XNA-based applications, and moves into more advance topics including gestures, using the accelerometer, integrating GPS features into your applications, working with data features, and much more. Kevin also covers some of the essentials for submitting your application to the Windows Phone Marketplace. Learn Windows Phone development at your pace ... get specific solutions whenever you need them! "--Resource description page.